Treatment Outcomes and Factors Associated with Treatment Outcomes among Patients Treated with Multidrug Resistant Tuberculosis Regimens, Ubon Ratchathani Province between 2016-2021 - Wongsa, Bhumiwasit; Sripa, Saksit; Akanit, Uraiwan (Journal of Disease and Health Risk DPC.3, 2024)
Objective: to study successful treatment outcomes and factors associated with treatment outcomes for patient who receive multidrug-resistant tuberculosis regimens in an Ubon Ratchathani province hospitals Methods: This was mixed methods research that combined quantitative and qualitative data collection. Quantitative data were collected from hospital medical records of 119 multidrug-resistant tuberculosis patients from October 1, 2016 to December 31, 2021. Qualitative data were collected from 30 multidrug-resistant tuberculosis patients including 15 treated with multidrug-resistant regimens and 15 medical professionals who take care of multidrug-resistant tuberculosis patients in Ubon Ratchathani province. Multivariate logistic regression was used to analyze the relationship among factors associated with successful treatment outcomes Results: The results of the quantitative study were found among 119 patients treated with multidrug-resistant regimens. A mean age of 47.99±16.52 years and a mean duration of treatment for multidrug-resistant tuberculosis (MDR-TB) of 15.89±8.09 months. Multidrug-resistant tuberculosis (MDR-TB) type were found the most for 91.58% and successful treatments were found for 73.11% of them. Factors that contribute to treatment not success included patients over 60 years of age and news patients with least two positive sputum smears. The qualitative results showed that a supportive system of health care service promotes treatment success. Conclusion: The improving patient compliance with medications and directly observed therapy (DOT) should be strictly followed for these patients.